Cavitation in internal flows of liquid jet through a throat - Hamid, Ahmad H. A.; Matali, Azmi A.; Kasolang, S.; Ghaffar, Z. A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The interaction of a liquid with the surrounding air produces unstable waves that disintegrate the liquid into droplets, which is known as liquid atomization. The common internal flow of a liquid atomization nozzle experiences a single-phase flow but might turn into a multiphase flow with the existence of cavitation. Cavitation in internal flow has gotten a lot of attention because of the positive and negative consequences it can have depending on the application. One such advantageous result is that cavitation has been used to promote the atomization of liquid jets by causing gas bubbles in the atmosphere to collapse. Most of the past research on cavitation has focused on the exit orifice’s constant cross-section area. The current study investigates the effect of throat location and geometry on cavitation characteristics. Filtered water was used as the simulation fluid. The high-speed shadowgraph technique was applied to record the images of the internal flow patterns. The placement of the throat was discovered to have a substantial impact on the status of the cavitation. Cavitation began at the inlet of the throat when the throat was placed at the uppermost part of the exit orifice. However, when the throat is placed in the middle of the exit orifice, the cavitation begins at the end of the throat. Four cavitation regimes were identified, namely developing, mixed, super and sudden expansion cavitation. Furthermore, it was found that the discharge coefficient depends on the cavitation’s state and length, except when the cavitation is in the supercavitation regime.